Sistem Monitoring Tumbuh Kembang Balita/Batita di Tengah Covid-19 Berbasis Mobile - Styawati Styawati; Fenty Ariany (Teknik Informatika Universitas Pamulang, 2020)
The Corona virus is growing rapidly throughout the world, including in Indonesia. The development of the virus causes many activities related to humans to be stopped first. One of the activities that is not allowed is Posyandu (Pos Pelayanan Terpadu), even though posyandu is very important to do. Due to the importance of the posyandu, the posyandu cadres conduct a mobile posyandu (sweeping). The problem that arises from sweeping is that people who have toddlers are not at home. Even though they are at home, they usually don't want to meet with posyandu cadres because they are afraid of the spread of the Corona Virus. Technological developments can help prevent the spread of the Corona Virus to humans. Any activity related to other people can be done online. In this study, trying to design a system that can monitor the growth of toddlers without having to meet directly with posyandu cadres. The system design is also expected to help Poskeskel (Pos Kesehatan Kelurahan) and Puskesmas (Pusat Kesehatan Masyarakat) to view and print weighing reports without having to ask for monthly weighing data reports for toddlers to Posyandu in Bandar Lampung. In addition, this system is expected to make it easier for posyandu cadres to report every posyandu activity and to report the growth and development of toddlers who are registered at the Flamboyan 9 Posyandu.